The Role of Auditor Reputation in Moderating the Effect of CSR and Earnings Management on Tax Avoidance - Kurniawati, Desi; Pertiwi, Indah (IJESS International Journal of Education and Social Science, 2024)
This study analyzed the effect of earning management and corporate social responsibility disclosure on tax avoidance moderated by auditor reputation. This study employed panel data from 12 Indonesia's mining companies from 2015 – 2019. This study used the effective tax ratio (ETR) as the proxy of tax avoidance. By employing the regression panel data analysis, this study found that earnings management has a negative and significant effect on ETR. Meanwhile, this study revealed that CSR could not affect the ETR. On the other hand, this study found that auditor reputation has a negative moderated role in the CSR's effect on ETR. Nevertheless, this study failed to prove any moderating role of auditor reputation in earnings management's effect on ETR. These results revealed that earnings management in mining companies was carried out in the context of tax avoidance.